Assessing the variability of soil nitrogen mineralization - Bohm, Sven (Kansas State University, 2007)
Variable N fertilizer application recommendations would benefit from crediting the N that will be mineralized and available to the crop during the growing season. During the 1994 and 1995 growing season, the spatial and temporal pattern of N mineralization was assessed on two central Kansas corn fields. Net N mineralization was measured in the field using a buried bag and a resin core method. A 60 m sampling grid was established on the field and the N mineralization was measured at each grid point. The field N mineralization measured was then compared to three lab incubation (14 day anaerobic incubation, CO₂ evolved 1 day after rewetting, and N released on autoclaving) measurements to determine if the field N mineralization could be predicted by a laboratory test. Nitrogen mineralization in the field was highest in May and declined during the growing seasons. Patches of high N mineralization appeared and disappeared during the season, areas of high and low mineralization were not found in the same areas month after month. The semivariance of the laboratory incubations tended to be smoother near the origin than the field incubations, indicating that the field incubations were subject to more sources of variability (such as microclimatic variations) than the laboratory incubations. Crop yields were not correlated with N mineralization in these fields. Soil moisture appeared to be more important to crop yields than the N contributed by mineralization. In these fields N mineralization does not need to be included in N fertilization recommendations unless the amount of fertilizer applied is much lower than in this study. Finally, a method to estimate the initial δ¹³ C content of a soil is proposed. This method can be used if a location can be found that has had a continuous C₃, a continuous C₄crop and a C₃/ C₄rotation treatment.
Keywords: Nitrogen mineralization; Variability; Agriculture, Agronomy (0285)